Community Diagnosis Program - A multi-professional education and team approach for medical, dental and nursing students - Jha, N (Health Renaissance, 2011)
Multi-professional Education (MPE) is now recognized as the cornerstone of community based education programs. This is especially important since there is a need for the various streams of training to appreciate the roles of each other. The objectives of this study were to know the students. feedback about the each component of Community Diagnosis Program (CDP) and to identify the knowledge and skills learnt by the students. A total 636 students from MBBS, BDS and B Sc Nursing students were posted together for the CDP in different years for various activities in the field. The students were asked to give their feedback by the help of semi-structured questionnaire given to them. The data were analyzed. All 636 students reported that the CDP was very useful. The knowledge and skills learnt by the student during this posting were communication skills, working in a team, collection, compilation, analysis and interpretation of data, health problems of the community, the socio-economic factors affecting health and diseases, skills related to organizing Focus Group Discussion, Health Education Session, Health Exhibition and Health checkup program and preparation and presentation of report. This CDP provides the students with a comprehensive picture of the health problems of the people, a clear understanding of the physical, socio-economic environmental factors affecting health of the people and health needs of the communities they would serve in future as health professionals. Keywords: community based education; community diagnosis medical education; community oriented program; multi-professional education; Nepal DOI: 10.3126/hren.v9i1.4361 Health Renaissance, 2011: Vol.9 No.1:41-44